Effects of enteral nutrition with parenteral glutamine supplementation on the immunological function in septic rats. Issue 11 (21st April 2015) - Fan, Jun; Wu, Lidong; Li, Guoping; Tao, Shaoyu; Sheng, Zhiyong; Meng, Qingyan; Li, Fengxin; Yu, Lijuan; Li, Li
Abstract : The aim of the present study was to investigate the effects of enteral nutrition (EN) with parenteral glutamine (GLN) supplementation on inflammatory response, lymphatic organ apoptosis, immunological function and survival in septic rats by caecal ligation and puncture (CLP). Male rats were randomly assigned into two experimental groups and two sham CLP control groups ( n 10 per group). After CLP or sham CLP model and nutrition programme were completed, the GLN concentrations of plasma and tissues and several indices of immunological function including serum Ig content, circulating lymphocyte number, the CD4:CD8 ratio, the neutrophil phagocytosis index (NPI), the organ index and apoptosis of thymus and spleen, and plasma cytokine levels were determined. Moreover, the survival in septic rats was observed. The results revealed that EN with parenteral GLN supplementation remarkably increased the GLN concentrations of plasma and tissues, serum Ig content, the circulating lymphocyte number, the CD4:CD8 ratio, the indexes of thymus and spleen, NPI and survival compared with the control group ( P < 0·05). In contrast, the apoptosis of thymus and spleen and the levels of TNF-α, IL-1β and IL-6 in plasma were obviously decreased compared with the control group ( P < 0·05). These results show that EN with parenteral GLN supplementation diminished the release of inflammatory cytokines, attenuated lymphatic organ apoptosis, enhanced the immunological function and improved survival in septic rats.